Heronamides G–L, polyene macrolactams from Streptomyces niveus. Issue 31 (9th May 2018) - Ding, Nan; Han, Li; Jiang, Yi; Li, Guiding; Zheng, Zehui; Cao, Bixuan; Guan, Peipei; Mu, Yu; Lin, Bin; Huang, Xueshi
Abstract : New polyene macrolactams, heronamides G–L (1–6 ) from the fermentation broth of Streptomyces niveus . Abstract : Six new polyene macrolactams, heronamides G–L (1–6 ), one new polyenoic acid derivative, niveamide B (10 ), together with four known compounds, BE-14106-6 (7 ), BE-14106 (8 ), GT32-B (9 ), and niveamide (11 ), were isolated from the fermentation broth of Streptomyces niveus . Their planar structures were elucidated by detailed analysis of spectroscopic data. The absolute configurations of compounds1–6 were determined by calculated ECD spectra and analysis of the possible biosynthetic pathways. Compounds1–6 and8–11 did not exhibit any significant antimicrobial activities, cytotoxicities, or inhibitory effects on lipopolysaccharide-induced NO production in BV2 microglial cells.